A STATE-OF-THE-ART REVIEW OF COLD-FORMED BUILT-UP BEAM SECTIONS - Swastika, Tri Widya; Purnomo, Heru; Ashadi, Henki Wibowo; Soekarno, Praganif (Applied Research on Civil Engineering and Environment (ARCEE), 2025)
Cold-formed steel (CFS) built-up beam sections have attracted significant attention in structural engineering due to their high strength-to-weight ratio, ease of fabrication, and cost efficiency. The most valuable is to specifically address the issue of torsional rigidity that occasionally occurs in single symmetrical or open sections. Utilizing screws, bolts, or spot welding as intermediate fasteners throughout the length of the member is crucial for connecting two single sections into a box section. This helps prevent the single sections from buckling independently by providing an intermediate fastener (a tie constraint at the screw). This paper presents a state-of-the-art review of cold-formed built-up beam sections, focusing on their structural behavior, design methodologies, and recent advancements. Various built-up configurations, including face-to-face, back-to-back, and boxed sections, are examined in terms of moment capacity, buckling modes, and failure mechanisms. A comprehensive analysis of experimental, numerical, and analytical studies is provided, highlighting key parameters affecting the performance of built-up beams, such as sectional geometry, flexural loading types, intermediate fastener types, screw spacing, built-up section types, and failure mode, encompassing 18 academic publications from 2009 to 2024, identifying gaps in existing design provisions for built-up sections. Future research directions are proposed, emphasizing the need for further investigations of cold-formed built-up beam sections. This review is a helpful resource for students, researchers, engineers, and industry professionals seeking to enhance the understanding and use of cold-formed built-up beam sections in modern construction.